The modern management of endometrial cancer - Catherine M. Holland; Henry C. Kitchener (Oncology Reviews, 2011)
Endometrial cancer is a relatively common gynecological cancer which is increasing in incidence. Survival rates are generally good for those with early disease but a significant minority of women have high risk or advanced disease. Better treatments are required to improve outcomes for these women. There is increasing interest in the use of chemotherapy and improved understanding of the molecular biology of endometrial tumours may pave the way for the use of therapeutic biologic agents that target specific molecular pathways. Recent years have seen greater emphasis on an evidencebased approach to the management of women with endometrial cancer. Extended surgery and adjuvant therapy are now used selectively after individual risk assessment for each woman and there is increased interest in the use of chemotherapeutic agents in the adjuvant setting. This review addresses the modern management of endometrial cancer in the light of available evidence and highlights areas of controversy.